(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
the formation of cancer can attack any organic system of the human body. And talking about the bird look mea that refers to the cancer that affects the blood cells. And as part of blood cancer it rapidly multiplies the cells and attacks the different aspects of the circulatory system. talking about the automatic detection we can detect the cancer that reduce the error and the results obtained from the microscopic images and even by the mistakes that have been occurred by the pathology pathologist that mainly defines the detection of leukemia and as a result. The detection Detection of Leukemia with the help of microscopic images with the help of microscope images as the images are pre processed and the noise is removed as the images are also segmented for the classification to form appropriate structures as it contains the components which is being classified as Eosinophil, Neutrophil, Lymphocyte, Basophil, and Monocytand we have used the back propagation algorithm for the training of the images and the accuracy is achieved is around 85%